Russian Federation : Financial Assessment Program: Detailed Assessment of Implementation: IOSCO Objectives and Principles of Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2016)
This paper assesses the level of implementation of the International Organization of Securities Commissions objectives and principles of securities regulation in the Russian Federation. The findings reveal that there is much that the Central Bank of Russia needs to accomplish if it is to approach good international practice as a securities regulator. Some of the most recent regulatory changes, such as those on credit rating agencies, are clearly based on international standards. In other areas, further initiatives will be required. These include identification of conflict of interest and improving management standards of professional market participants.